Feed resources, feeding system and feed balance of dairy cattle in Chencha District, Southern Ethiopia - Kechero Yisehak; Kore Adane (Veterinary Medicine and Science)
Abstract Background Dairy cattle feed supplies in the tropics, and particularly in Ethiopia, are mostly derived from base diets (natural and improved grasslands, agricultural wastes, fodder trees and shrubs), agro‐industrial by‐products and non‐conventional feeds. The availability of major feed resource kinds, sources and dairy cattle feeding practises is primarily influenced by agro‐ecology and season, as well as their interactions. Objectives The research was carried out in the Chencha District of Gamo Zone, Southern Ethiopia, with the goals of assessing the available, feeding system, opportunity, limits and copying strategy of dairy cattle production, as well as estimating feed balance. Methods Data were gathered through primary and secondary data sources, field observations, key informant interviews, focus group talks and individual interviews. The survey data were stratified into altitudes, coded and analysed using the Statistical Package for Social Sciences version 20 and the general linear model approach. Cross‐tabulation was used to examine the statistical variance of categorical data. Results The presence of different feed resource types, distinct agro‐ecologies (p < 0.05) and crop residue accessibility were the major opportunities for dairy cattle production in the study district, but land scarcity, a lack of dry season forages and land degradation due to erosion were the major constraints for dairy cattle feed production. In the research district, the main feed resource–copying approaches were reducing the number of dairy animals, saving optional feeds and purchasing optional feeds. The total mean of dairy cow feed supply to tropical livestock unit in terms of dry matter (DM) production each year was 3.86 t of DM/HH/annual, with a negative feed balance of 8.09 t that varied with seasons and agro‐ecology (p < 0.05). Conclusions According to the findings of this study, the low production of dairy cattle in the district is clearly related to the scarcity of feed resources. To address these issues, alternative feed production technologies should be implemented, such as farmers practising forage development on their own crop land and collecting crop residues during crop harvesting times and storing them under shed; the nutritive value of different types of fodder trees and shrubs should be further determined in the future and feed storage methods, particularly hay and silage, should be used when there are an abundance of feed resources available.